2017
DOI: 10.1002/jclp.22527
|View full text |Cite
|
Sign up to set email alerts
|

Using interpersonal process recall to compare patients’ accounts of resistance in two psychotherapies for generalized anxiety disorder

Abstract: In a trial examining whether cognitive-behavioral therapy (CBT) could be improved by integrating motivational interviewing (MI) to target resistance, MI-CBT outperformed CBT over 12-month follow-up (Westra, Constantino, & Antony, 2016). Given that effectively addressing resistance is both a theoretically and an empirically supported mechanism of MI's additive effect, we explored qualitatively patients' experience of resistance, possibly as a function of treatment. For 5 patients from each treatment who exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(25 reference statements)
0
6
0
1
Order By: Relevance
“…With respect to related therapist actions, clients have indicated that they benefit when therapists listen, affirm, validate, empathize, reassure, demonstrate positive regard, and convey acceptance. Additionally, clients have expressed that therapists collaborating with them on the goals and tasks of therapy and granting them autonomy over the treatment's direction is helpful (e.g., Levitt et al, 2016;Morrison et al, 2017). These findings corroborate the robust quantitative literature that links similar researcher-or therapist-constructed factors, including the higher quality alliance (Flückiger et al, 2018) and goal consensus or collaboration (Tryon et al, 2018) with adaptive treatment outcomes.…”
Section: Helpful Eventsmentioning
confidence: 65%
“…With respect to related therapist actions, clients have indicated that they benefit when therapists listen, affirm, validate, empathize, reassure, demonstrate positive regard, and convey acceptance. Additionally, clients have expressed that therapists collaborating with them on the goals and tasks of therapy and granting them autonomy over the treatment's direction is helpful (e.g., Levitt et al, 2016;Morrison et al, 2017). These findings corroborate the robust quantitative literature that links similar researcher-or therapist-constructed factors, including the higher quality alliance (Flückiger et al, 2018) and goal consensus or collaboration (Tryon et al, 2018) with adaptive treatment outcomes.…”
Section: Helpful Eventsmentioning
confidence: 65%
“…Data were extracted and analysed using a combination of grounded theory analysis (GTA; Glaser, 1978;Glaser & Strauss, 1967) and consensual qualitative research methods (CQR; Hill, 2012), a hybrid approach used in other qualitative studies of psychotherapy constructs (e.g. Morrison et al, 2017;Westra et al, 2010). As was done in these studies, this blended method allowed us to take advantage of the open coding of grounded theory, while using CQR methods to obtain multiple perspectives on the data.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that ambivalence levels are higher at the beginning of therapy and in most of the cases are essential to initiate the process of change (Button et al, 2014; Miller & Rollnick, 2002; Morrison et al, 2017; Oliveira et al, 2021). However, a decrease in ambivalence has been observed in recovered clients, while unchanged clients tended to experience the same levels of ambivalence throughout treatment (Braga et al, 2019; Braga, Ribeiro, et al, 2018).…”
Section: Ambivalence In Psychotherapy: a Predictor Of Premature Termi...mentioning
confidence: 99%